ENDOTHELIAL DYSFUNCTION MARKERS IN PATIENTS WITH NON-ST ELEVATION ACUTE CORONARY SYNDROME AND MULTIFOCAL ATHEROSCLEROSIS - S. A. Berns; E. A. Schmidt; E. S. Yukhno; E. S. Kiprina; O. L. Barbarash (Российский кардиологический журнал, 2013)
Aim. To investigate the association between endothelial dysfunction markers and multifocal atherosclerosis in non-ST elevation acute coronary syndrome (NSTE- ACS). Material and methods. The study included 82 patients with NSTE-ACS, who underwent coronary angiography, colour duplex ultrasound of brachiocephalic arteries (BCA) and lower extremity arteries (LEA), and a complex assessment of endothelial function during their hospitalisation. Vasodilating endothelial function was assessed by endothelium-dependent vasodilatation (EDVD) in a reactive hyperemia test. Vasoconstrictory and adhesive endothelial function was assessed by the blood levels of endothlin-1, sP-selectin, and sE-selectin in a solid-phase enzyme immunoassay. Statistical analyses were performed using the STATISTICA 6.0 software package. Results. Isolated coronary artery (CA) atherosclerosis was registered in 46,3% of the patients, while isolated BCA atherosclerosis was observed in 9,7%, and the combination of CA and peripheral artery atherosclerosis was registered in 19,5%. No cases of isolated LEA atherosclerosis were observed. According to the visualisation results, 24,3% of the patients had no signs of atherosclerotic stenosis (>30%) in any vascular basin. The highest levels of endothelin-1 were registered in patients with isolated BCA atherosclerosis and with the combination of peripheral and CA atherosclerosis. No significant differences were observed between the groups by the blood levels of sP-selectin and sE-selectin; moreover, these levels were within the reference range. All groups demonstrated similar levels of vasodilating endothelial function. Conclusion. In NSTE-ACS patients, vasoconstrictory endothelial function was clearly associated with the atherosclerosis parameters. At the same time, there was no link between the atherosclerosis severity and localisation and the parameters of vasodilating and adhesive endothelial function. Endothelin-1, as a vasoconstriction marker, was most informative in patients with peripheral and multifocal atherosclerosis.